Integrating STEAM in Teaching Integrals: An Interactive Media Needs Analysis to Enhance Creative Thinking - Limori, Masako; Siswanto, Deny Hadi; Shigematsu, Taiyu; Astiwi, Wuri (RUKASI: Jurnal Ilmiah Perkembangan Pendidikan dan Pembelajaran, 2025)
This study aims to identify the current conditions of mathematics learning, the obstacles faced by teachers and students, and students’ perceptions regarding the need for innovative and interactive learning materials. The focus of this research is the development of an Integral e-module based on the STEAM approach as an effort to stimulate students’ creative thinking skills. The research employed a qualitative descriptive method, with data collected through interviews with mathematics teachers and questionnaires distributed to 30 students of class XI MIPA 2 at SMA Muhammadiyah Pakem. The findings reveal that most students experience difficulties in understanding Integral material due to the predominance of lecture-based instruction, unengaging teaching materials, and the limited use of interactive media. A total of 61% of students expressed a preference for e-modules as more favorable learning resources, while teachers acknowledged the importance of developing contextual and activity-based e-modules. The STEAM approach is considered relevant as it connects mathematical concepts with real-life contexts and fosters students’ creativity. Therefore, the development of an interactive STEAM-based e-module is regarded as a pedagogical solution to create mathematics learning that is more engaging, effective, and responsive to the challenges of the 21st century